Institution Building without Commitment - Bassetto, Marco; Huo, Zhen; Ríos-Rull, José-Víctor (American Economic Review, 2024)
We propose a theory of gradualism in the implementation of good policies, suitable for environments featuring time consistency. We downplay the role of the initial period by allowing agents both to wait for future agents to start equilibrium play and to restart the equilibrium by ignoring past history. The allocation gradually transits toward one that weighs both short- and long-term concerns, stopping short of the Ramsey outcome but greatly improving upon Markovian equilibria. We use the theory to account for the slow emergence of both climate policies and the reduction of global tariff rates. (JEL C73, E21, E61, F13, H30)